Analisis peningkatan kinerja desain Bangunan Gedung DPRD Kabupaten Sumenep berdasarkan prinsip bangunan gedung hijau (BGH) - Masmulyadi; F. Rooslan Edy Santosa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
The implementation of Green Building (BGH) has become an important strategy for improving resource efficiency and supporting sustainable development in the construction sector. Although BGH regulations are mandatory for state-owned buildings in Indonesia, empirical evidence on the effectiveness of design revisions in enhancing building performance during the technical planning stage remains limited. This study evaluates the effectiveness of regulation-based design revisions in improving Green Building performance, quantifies performance changes, and identifies the assessment aspects that most influence BGH achievement. A regulatory-based performance assessment with a before–after comparative case study design was applied to the Sumenep Regency DPRD Building. Building performance was evaluated using the official BGH assessment system established under Minister of PUPR Regulation No. 21/2021 and Ministerial Circular No. 01/SE/M/2022. Performance changes were measured by comparing the initial and revised design scores using absolute and relative improvement indicators across seven BGH assessment aspects. The results indicate that the BGH score increased from 70 points (42.4%) to 124 points (75.2%), upgrading the building classification from non-compliant to the Madya Green Building category. The improvement was mainly driven by energy efficiency measures, including optimization of building orientation, lighting, and air-conditioning systems, while water efficiency showed only limited progress. These findings demonstrate that regulation-based design revisions not only improve compliance with BGH requirements but also function as a strategic mechanism for enhancing sustainability performance from the planning stage. This study contributes a regulatory-based comparative evaluation approach for quantitatively assessing design revision effectiveness and identifying the dominant factors influencing Green Building performance in regional government buildings.